The Effect of Return on Assets and Earnings Per Share on the Stock Price of PT Unilever Indonesia, TBK for the Period 2014-2022 - SUHARTINI, Titin; HIMMY’AZZ, Istajib Kulla; BRILLIANT, Shelly; SHODIQ, Muhammad Zacky Syauqy Ibnu; TYAS, Stephanie Dwi Wahyuning (Journal of Governance, Taxation and Auditing, 2025)
The stock price of PT Unilever Indonesia, Tbk fluctuated from 2014 to 2022. The stock price fluctuation of PT Unilever Indonesia, Tbk is thought to be influenced by profitability ratios, namely Return On Assets and Earnings Per Share. This study aims to determine the effect of Return On Assets (ROA) and Earnings Per Share (EPS) on the stock price of PT Unilever Indonesia, Tbk. The data used are secondary data, namely, financial reports. The population used is the financial statements of PT Unilever Indonesia, Tbk, and the sampling method uses purposive sampling. The analysis techniques used are descriptive statistical tests, classical assumption tests (normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests), correlation tests, coefficient of determination tests, and hypothesis tests using Statistical Product and Service Solutions (SPSS) version 18 with a significance level of 5%. The results of the hypothesis test show that partially, ROA has no significant effect on Stock Prices, and EPS has a significant effect on Stock Prices. While simultaneously, ROA and EPS have a significant effect on Stock Prices.